UTeM's Undergraduate Experience on Facebook: Preliminary Findings - Kalthom, Hussain; aida nasirah , abdullah; Hanipah, Hussin; hazmilah, hasan (2010)
Social network sites are becoming more popular and are being used by different groups of people. A market study conducted by Nickburcher (2009) on facebook usage reported that there are now 27 countries with over 1 million people using facebook. Malaysia was reported to have 1,069,260 million of people log on to facebook by March 2009. Among the popular social networking sites are facebook, MySpace and Twitter. However, in Malaysia little is known about how much, why and how users use Facebook. In this study, 100 engineering undergraduates comprises of 50 males and 50 females of Universiti Teknikal Malaysia Melaka completed their reflecting journaling method across five days and supplemented by survey were completed, reporting the prevalence and time spent, why and how they use the facebook. Preliminary findings of the study indicated that females participants spent more often for social interaction with whom they have built offline relationship. Implications of facebook use for the development of identity and peer relationships are discussed.